2004
DOI: 10.1002/num.20030
|View full text |Cite
|
Sign up to set email alerts
|

High‐order numerical methods for one‐dimensional parabolic singularly perturbed problems with regular layers

Abstract: In this work we construct and analyse some finite difference schemes used to solve a class of timedependent one-dimensional convection-diffusion problems, which present only regular layers in their solution. We use the implicit Euler or the Crank-Nicolson method to discretize the time variable and a HODIE finite difference scheme, defined on a piecewise uniform Shishkin mesh, to discretize the spatial variable. In both cases we prove that the numerical method is uniformly convergent with respect to the diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…As the exact solutions of the IBVPs (5.1) and (5.2) are not known, we illustrate the numerical results of the upwind scheme (3.9) by using the double mesh principle as in [2] which is described below.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…As the exact solutions of the IBVPs (5.1) and (5.2) are not known, we illustrate the numerical results of the upwind scheme (3.9) by using the double mesh principle as in [2] which is described below.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…3. As the exact solutions of Examples 6.1 and 6.2 are not known, to show the ε-uniform convergence of the proposed scheme (4.1) and also to obtain the accuracy of the numerical solutions, we use the double mesh principle as in [7] which is described below. with N mesh-intervals in the spatial direction and M mesh-intervals in the t-direction such that t = T/M is the uniform time step.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…where L ε u(x, t) ≡ −εu xx (x, t) + a(x)u x (x, t) + b(x, t)u(x, t), (2) with a(x) > α > 0 and b = b(x, t) ≥ 0 onΩ. The diffusion coefficient ε is a small positive parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In two recent papers (Clavero et al (2005) [2] and Mukherjee and Natesan (2009) [3]), this method has been shown to be convergent, uniformly in the small diffusion parameter, using somewhat elaborate analytical techniques and under a certain mesh restriction. In the present paper, a much simpler argument is used to prove a higher order of convergence (uniformly in the diffusion parameter) than in [2,3] and under a slightly less restrictive condition on the mesh.…”
mentioning
confidence: 98%